PENGARUH LAYANAN BIMBINGAN KELOMPOK MELALUI TEKNIK DISKUSI TERHADAP SISWA YANG MENGALAMI KEJENUHAN BELAJAR DI KELAS VIII MTs AL-WASHLIYAH BANGUN PURBA TAHUN AJARAN 2021/2022 - Riska Yolanda; Nur Asyah (Jurnal Inovasi Penelitian, 2022)
This study aims to analyze students who experience learning saturation before and after the service is provided and is there any effect of group discussion techniques on students who experience learning saturation in class Vlll MTS Al-Washliyah Bangun Purba. This type of research is quantitative pre-experimental with the One Group Pre-test Post-test Design method. The population of this study was 36 students of class VII MTS, sampling by purposive sampling method was 10 students. The research data was collected using an instrument or a learning saturation questionnaire with a Likert scale, the statement items totaled 37 items that were valid and reliable and then the data were analyzed using the Wilcoxon test. The resulting data shows that there are differences in students who experience learning boredom in class Vlll MTS Al-Washliyah Bangun Purba before and after being provided with discussion technique group guidance services. From data analysis obtained Asymp.Sig.(2-tailed) is worth 0.000. Because 0.000 is smaller than <0.05 so Ho is rejected and Ha is accepted. So it can be concluded that there are differences in students who experience learning boredom before and after being given group guidance services with discussion techniques. effective to reduce students who experience learning saturation.